EVALUASI KINERJA UNIT BISNIS ASPHALT MIXING PLANT PT PRAYOGA PERTAMBANGAN DAN ENERGI - Raden Isma Anggraini; Aida Vitayala Hubeis; Radjab Tampubolon (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2016)
Currently, the mining sector is still one of the main sectors driving the economy of Indonesia and is in demand by both indigenous and foreign investors. Asphalt mixing plant business unit (AMP BU) is currently the main priority scale of PT Prayoga. The AMP UB excellent performance of PT Prayoga enable itself to be able to contribute to the company's revenue and accelerate development of infrastructure in Bogor. The objectives of the research were to identify key performance indicator (KPI) that is applied in the financial and non-financial perspectives as well as to evaluate the performance of UB AMP of PT Prayoga in terms of financial and non-financial aspects based on the vision, mission and strategy of the company. The method used in this research was the balanced scorecard as a management tool to maintain a balance between the financial (financial perspective) and non-financial (customer perspective, business processes, learning and growth) indicators. The results showed that the KPI applied in the evaluation of the performance of AMP BU of PT Prayoga consists of 19 indicators including 5 KPI of financial perspective, 5 KPI of customer perspective, 5 KPI of business process perspective, and 4 KPI of learning and growth perspective. The assessment results indicate this business unit obtained the performance index of 78.42% included in the criterion of very good or excellent, thus it has shown its best performance according to the vision, mission and strategy of the company.Keywords: balanced scorecard, performance assessment, performance index, KPI, mining